Cross-Cultural Perspectives of Southeast Asian Countries on Physical Education Curriculum: A Scoping Review - Catahan, Gideon L.; Mangulabnan, Leslie P.; Visda, Vincent Brian L.; Perez, Decerie C.; Tolentino, Julius Ceazar G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The physical education curriculum varies across cultures worldwide, with this scoping review focusing specifically on Southeast Asia. The study aims to analyze published research that highlights how South-east Asian nations perceive the physical education curriculum, as well as the challenges they face in this field. The findings are evaluat-ed to identify practices and strategies that neighboring countries might adopt to address local challenges. Additionally, the review serves as a basis for assessing the current state of relations among the countries in the region. The scoping review follows the frame-work proposed by Arksey and O’Malley, encompassing stages from formulating research questions to summarizing findings obtained through data charting. The results indicate that Southeast Asian countries are committed to improving their physical education cur-ricula, consistently investing in planning and implementation. How-ever, the challenges vary across nations, ranging from limited tech-nological advancements to issues in curriculum design and execu-tion. Analyzing existing literature reveals strategies that could help countries overcome local obstacles. Sharing these insights has the potential to strengthen regional collaboration and contribute to the overall development of the physical education curriculum in South-east Asia.